The Spanish "Century XXI" academy for developing elite level basketballers: design, monitoring and training methodologies - Calleja-Gonzalez, J.; Mielgo-Ayuso, J.; Lekue, J. A.; Leibar, X.; Erauzkin, J.; Jukic, I.; Ostojic, S. M.; Delextrat, A.; Sampaio, J.; Terrados, N. (The Physician and Sportsmedicine, 2016)
Objectives: The XXI Century Academy was a 6-year state-initiated intervention program that served as an alternative to basketball clubs for players in the u-14 and u-18 age groups in Spain, under guidelines established by the Spanish Basketball Federation. It was an important and unique project on talent development in basketball. To the best of the authors` knowledge, no evidence has been reported on long-term athlete development programs in basketball worldwide. The main aim of this report is to describe the design and evaluation methods used for the XXI Century Academy as a long-term intervention program in the elite Spanish Basketball Academy, aiming to prepare basketball players to compete at the elite level.